An efficient single‐cell based method for linking human T cell phenotype to T cell receptor sequence and specificity. Issue 2 (15th November 2021) - Wahl, Ilka; Hoffmann, Sandro; Hundsdorfer, Rebecca; Puchan, Julia; Hoffman, Stephen L.; Kremsner, Peter G.; Mordmüller, Benjamin; Busse, Christian E.; Wardemann, Hedda
Abstract: Single‐cell antigen‐receptor gene amplification and sequencing platforms have been used to characterize T cell receptor (TCR) repertoires but typically fail to generate paired full‐length gene products for direct expression cloning and do not enable linking this data to cell phenotype information. To overcome these limitations, we established a high‐throughput platform for the quantitative and qualitative analysis of human TCR repertoires that provides insights into the clonal and functional composition of human CD4 + and CD8 + αβ T cells at the molecular and cellular level. The strategy is a powerful tool to qualitatively assess differences between antigen receptors of phenotypically defined αβ T cell subsets, e.g. in immune responses to cancer, vaccination, or infection, and in autoimmune diseases. Abstract : Here, we describe a high‐throughput platform linking the human T cell phenotype to TCR genotype and specificity at single‐cell level. Single T cells are isolated by flow cytometry and paired TRA and TRB genes are amplified and sequenced. TCR reactivities are determined by large‐scale TCR expression cloning and functional assessments.